2012
DOI: 10.1186/1546-0096-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Differential manifestations of prepubescent, pubescent and postpubescent pediatric patients with systemic lupus erythematosus: A retrospective study of 96 Chinese children and adolescents

Abstract: BackgroundChildren represent 10-20% of all systemic lupus erythematosus (SLE) patients. Their clinical manifestations and outcomes vary with age. We aim to clarify the relationship between pubescent status and the clinical manifestations of pediatric SLE.MethodsIn this study, pediatric SLE patients were divided into three groups, based on age at disease onset (≦8, 8–13 & 13–18 years), defined as prepubescent, pubescent and postpubescent, respectively. Initial clinical manifestations and laboratory characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
3
14
0
6
Order By: Relevance
“…Previous retrospective studies suggested that age at disease onset (10)(11)(12)(13) and age at diagnosis (9) may influence disease expression in terms of initial clinical presentation, pattern of organ involvement and serological findings. The small sample size of these studies performed in North America, Europe and Asian cSLE populations (8)(9)(10)(11)(12)(13) precludes a definitive conclusion about their findings, particularly regarding the early-onset cSLE patients (<6 years).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous retrospective studies suggested that age at disease onset (10)(11)(12)(13) and age at diagnosis (9) may influence disease expression in terms of initial clinical presentation, pattern of organ involvement and serological findings. The small sample size of these studies performed in North America, Europe and Asian cSLE populations (8)(9)(10)(11)(12)(13) precludes a definitive conclusion about their findings, particularly regarding the early-onset cSLE patients (<6 years).…”
Section: Introductionmentioning
confidence: 99%
“…The small sample size of these studies performed in North America, Europe and Asian cSLE populations (8)(9)(10)(11)(12)(13) precludes a definitive conclusion about their findings, particularly regarding the early-onset cSLE patients (<6 years). In addition, there is no published data on the relevance of age in a large cohort of Latin-American cSLE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interpreting such definitions would seem to require clarification of prepubescent. The age of puberty can vary from person to person, but a recent article in a paediatric journal suggested "patients ≦ 8years old (prepubescent), [8][9][10][11][12][13] (pubescent), 13-18 (post-pubescent)" [7]. It is possible that these age ranges suit the country and the study, but they appear unduly low and it may be more typical to distinguish amongst those sexually attracted to infants from 0-5 years, (called Nepiophilia or infantophilia), children younger than 11 (Paedophilia, which may incorporate Nepiophilia), ages 11-14 (Hebephilia) and 15-19 (Ephebophilia) e.g.…”
Section: Paedophile Hebephile or Child Sexual Offender?mentioning
confidence: 99%
“…Системная красная волчанка (СКВ) -системное ауто-иммунное заболевание с мультиорганным вовлечением, поражающее до 10-20% детей [1]. Клинические прояв-ления СКВ крайне вариабельны, течение зачастую мало предсказуемо; имеет тенденцию к более тяжелому течению при возникновении в детском возрасте [2][3][4].…”
Section: Introductionunclassified